Is Our Understanding of Solar-Wind/Magnetosphere Coupling Satisfactory? - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2021)
An assessment of our physics-based understanding of solar-wind/magnetosphere coupling finds that the understanding is not complete. Solar-wind/magnetosphere coupling is foundational to magnetospheric physics and it is a key to comprehending and predicting space weather. We are modestly successful at correlating solar-wind variables with geomagnetic indices, but we lack the full knowledge to describe in detail how the shocked solar-wind plasma transports mass, momentum, and energy into the magnetosphere-ionosphere system and how the shocked solar wind drives geomagnetic activity and magnetospheric evolution. The controlling solar-wind factors that govern the driving of the magnetosphere-ionosphere system are not accurately known. Without this knowledge accurate predictions of the magnetospheric behavior cannot be made and no magnetosphere-ionosphere model will work correctly if it is driven incorrectly. Further, without a fundamental understanding, the prediction of the system reaction to some as-yet-unseen extreme solar-wind conditions will not be possible. In this perspective article several gaps in our knowledge are catalogued. The deficiencies in our physical understanding of solar-wind/magnetosphere coupling constitute a major unsolved problem for space physics (and for astrophysics), a problem that demands enhanced, coordinated research.